Integrated analysis of microbiome and host transcriptome revealed correlations between tissue microbiota and tumor progression in early-stage papillary thyroid carcinoma - Xiuwen Tong; Xiuwen Tong; Xipei Chen; Chen Shen; Jiahao Pan; Xinyu Wang; Xinyun Xu; Sheng Liu (Frontiers in Cellular and Infection Microbiology)
IntroductionEmerging evidences suggest that microorganisms in the tumor microenvironment play important roles in tumor occurrence and progression. However, the microbial distribution in the papillary thyroid carcinoma (PTC) tissue and its relationship with PTC are unclear.MethodsWe performed 16S rRNA amplicon sequencing and RNA-Seq to characterize the tissue microbiome and transcriptome between the tumor and paracancerous tissue, respectively. The association analysis between microbes and host gene expression were conducted to screen the potential microbe-gene/cell interactions.ResultsWe found that the tumor tissues indeed harbored complex microbial communities, which showed significant differences in microbial and functional composition between the tumor and para-cancerous tissues. A set of differential microbial genera were identified to be significantly associated with the clinical factors, such as Planococcus enriched in tumor tissue, Limnobacter in T1a stage and Cutibacterium in N1b stage. 793 differential expressed genes were also identified, which are mainly enriched with functions related to cell-cell communication and extracellular matrix. In terms of the immune cell composition, 8 differential immune cell types were further identified, suggesting a significant immune response in PTC. Finally, association analysis identified 5 pairs of microbe-gene association and 1 pair of microbe-cell with significance, which were all involved in the tumorigenesis and tumor progression via inflammation-related pathways.ConclusionsIn addition to characterizing the tissue microbiome and host gene expression in PTC patients, we further explored the roles of microbe-gene/cell interactions in PTC. The results provide candidate biomarkers for exploring the molecular mechanisms of tissue microbiome in tumorigenesis and tumor progression of PTC.